The prevalence of visual axis opacification in the Swedish Pediatric Cataract Register - Magnusson, Gunilla; Gyllén, Jenny; Haargaard, Birgitte; Nyström, Alf; Rosensvärd, Annika; Scurei, Carmen; Kjellström, Ulrika; Tornqvist, Kristina (Acta Ophthalmologica, 2024)
Purpose: To report on the occurrence of postoperative visual axis opacification (VAO) in children younger than 5 years of age operated for cataract in Sweden, and to analyse correlations with age at surgery and surgical method. Methods: Data were derived from the Swedish Pediatric Cataract Register (PECARE). All children operated on between 1 January 2007 and 31 December 2020 were included. Follow-ups at 1, 2 and 5 years of age were analysed. Results: Cataract surgery were performed on 770 eyes belonging to 549 children (n = 282 boys, 51.4%); 327/770 (42.5%) of the children underwent surgery before 3 months of age and 216/770 (28%) before 6 weeks of age. Data on 881 follow-up visits were registered. At the follow up-visits at 1, 2 and 5 years of age, VAO was present in 154/349 (44.1%), 41/323 (12.7%) and 25/208 (12%). The majority of the children with VAO underwent cataract surgery before age 6 months, with a predominance before age 2 months. Primary IOL was implanted in 601/770 (78%) of eyes; 40.8% had an acrylic one-piece lens, 31.8% had a bag-in-the-lens IOL, 21.9% were aphakic and 5.2% had an acrylic three-piece lens. Implantation of a bag-in-the-lens IOL was related to a significantly lower occurrence of VAO compared to other types of IOL, including aphakia (p < 0.0002). Conclusion: Our results are in accordance with the literature. Primary bag-in-the-lens IOL implantation before 2 years of age seems adequate and safe, with a low occurrence of VAO, and can thus be continued as routine in Sweden.
Keywords: congenital; lens surgery; paediatric cataract; postoperative complication; visual axis opacification